Development of “Active Consumer” Concept on Energy Market - Firsova, Irina A.; Vasbieva, Dinara G.; Losyakov, Andrey V.; Arhipova, Viktoriia S.; Pavlushin, Andrey A. (International Journal of Energy Economics and Policy, 2018)
The paper investigates a new approach to interaction of all participants on the energy market. An active consumer, as a participant of the energy market, has technical capabilities for optimization of their energy consumption, and determines whether "to produce" or "to buy" electrical energy on the market by themselves. The active consumer’s profile reflects their ability to optimize the electrical energy consumption schedule to improve the economic efficiency of consumption and reduce the cost of the electrical energy consumed. In the concept proposed in this paper, the active consumer is considered as a partner of the energy market entities. This brings about a change in the market regulators and participants’ behavior and their transition from the concept of cost management to the concept of interaction with consumers, involving them in the value chain. A significant difference in the cost of electrical energy for domestic and foreign industrial companies, due to the development of new technologies in the energy sector, leads to a change in the participants’ behavior. Within the framework of the active consumer concept, we propose a process model for the participants’ behavior in the energy market, which presents the economic benefits to all participants during a particular period of time. Keywords: Active Consumer, Energy Market, Demand-Side Management, Economic Benefits. JEL Classifications: D24; Q43; M31